2012
DOI: 10.1210/jc.2011-3169
|View full text |Cite
|
Sign up to set email alerts
|

Ten Novel Mutations in the NR5A1 Gene Cause Disordered Sex Development in 46,XY and Ovarian Insufficiency in 46,XX Individuals

Abstract: SF-1/NR5A1 mutations are frequently found in 46,XY DSD individuals (9%) and manifest with a broad phenotype. Testes histology is characteristic for fat accumulation and degeneration over time, similar to findings observed in patients with lipoid congenital adrenal hyperplasia (due to StAR mutations). Genotype-structure-function-phenotype correlation remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
157
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(177 citation statements)
references
References 42 publications
18
157
2
Order By: Relevance
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, interallelic association with the known p.Gly146Ala polymorphism (rs1110061) may further reduce NR5A1 activity and contribute to more severe phenotypes (WuQiang et al, 2003; Hasegawa et al, 2004; Wada et al, 2006; Reuter et al, 2007; Köhler et al, 2008; Lourenço et al, 2009; Bashamboo et al, 2010a; Paris et al, 2011; Camats et al, 2012). However, two patients in our cohort also bore the p.Gly146Ala variant besides the pathogenic NR5A1 variants, p.Trp302Cys and p.Tyr404*, and their phenotype was not strikingly distinct or more severe.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was shown that NR5A1 mutations are also a genetic cause of POI, with phenotypes ranging from primary to secondary amenorrhea, associated with infertility, hypoestrogenism, and elevated gonadotropin levels (Lourenço et al, 2009; Camats et al, 2012) Sisters and mothers of 46,XY DSD patients carrying heterozygous NR5A1 mutations may also develop premature ovarian failure (Lourenço et al, 2009; Camats et al, 2012; Fabbri et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no clear genotype-phenotype correlation could be detected in patients with NR5A1 mutations. However, in patients with severe forms of 46,XY DSD, previously described mutations are mostly missense mutations in the DNA-binding region (including its accessory DNA-binding domain) or in the ligand-binding domain as well as nonsense mutations leading to severe changes of the protein (8,10,16,21,30,31,32,33,36,37,38,39).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…The phenotypic spectrum has been extended, involving not only ambiguous genitalia and hypospadias due to gonadal dysgenesis (8,9,10), but also vanishing testis syndrome (11), isolated hypoplastic penis (12) and male infertility (13,14). Moreover, NR5A1 mutations were also found in 46,XX females with premature ovarian failure and primary ovarian insufficiency (15,16,17,18,19). Altogether, NR5A1 mutations have emerged as being the most frequent cause (6.5-15%) of different phenotypes of 46,XY DSD in Western countries.…”
Section: Introductionmentioning
confidence: 99%